Tipton, Mitchell County - Bechard, Austin (Kansas State University, The Chapman Center for Rural Studies, 2012)
William A. Pitt and fellow settlers from Trier, Germany, first settled near Carr Creek, but flooding encouraged them to relocate to the top of a nearby hill. They called their settlement Pittsburg and, later, Tipton.
Austin Bechard, “Tipton, Mitchell County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/142.
Keywords: German Immigrants; Kansas; Mitchell County; Tipton; Pittsburg; immigrants